RANCANG BANGUN DAPUR CRUCIBLE TIPE PENUANGAN TUNGKIK KAPASITAS 15 KG DENGAN BAHAN BAKAR GAS LPG - Ipung Kurniawan; Bayu Aji Girawan; Saeful Nurrohman (P3M Politeknik Negeri Cilacap, 2018)
This research aims to; 1) Designing and making aluminium melting crucible casting with the capacity15 kg; 2) Conducting the test of chemical composition of the first and second melting result. Theresearch used field and library research. From the result of the design, it could be obtained that thedimension of melting casting has 547 mm diameter, 3 mm thick, 410 mm high. Whereas, molten cup has 178 mm diameter, 8 mm thick, and 230 mm high. The result of the first melting chemicalcomposition test and the second one do not work out a significant change. The material of the firstmelting result still contains 89,52% of aluminium (Al), while the main fusion is 7,71% of zinc (Zn)and 1,84% of silicon (Si), and in the second melting result still contains 89,55% of Alumunium (Al),while the main fusion is 7,51% of zinc (Zn) and 1,94% of silicon (Si).